Variation in Bifurcation Pattern of Brachial Artery - Alborz Jafaee Soog; Ebrahim Kharazinejad; Forouzan Absalan (Anatomical Sciences Journal, 2018)
Recognizing the arterial variations of human upper extremities is of potential clinical practice because this area is involved in arterial handling and invasive medical procedure. During dissection of the left upper limb of a 35-year-old male embalmed cadaver, we saw brachial artery bifurcation in the middle third of proximal portion of the arm. Its medial branch descended along the medial side of the arm, medial to the median nerve. This branch then redirected laterally after crossing with median nerve. In this part, it lied posterior to the nerve until reached the lateral aspect of the arm. At the elbow level, the medial branch continued as radial artery. The lateral branch of brachial artery remained lateral to the median nerve until reached the elbow. In this part, it continued as ulnar artery after crossed the median nerve anteriorly and descended as interosseous artery.